Tales of two city-states : the development progress of Hong Kong and Singapore - Geiger, Theodore; Geiger, Frances M. (Washington : National Planning Association, 1973)
This book is about macro social organization that is rare in the modern world, the development progress of Hong Kong and Singapore.
Includes bibliographical references and index.
oo 01/08/2018
Loans
Keywords: Economic history; Hong Kong (China).; Singapore